Princess Sodara Kartika frees Amir from prison; The epic of Amir Hamza (?16th century) - Arps, Bernard (UI Scholars Hub, 2021)
MS Jav. b. 2 (R) is among the earliest Javanese manuscripts brought to Europe by seafarers. It was presented to the Bodleian Library, Oxford, in 1629. Its text – titled Stories of Amir (Caritanira Amir) – sheds new light on the literary and cultural history of Java and the wider Java Sea world. Probably composed in the 1500s, possibly in Banten, the text contains part of an adaptation of the Malay Hikayat Amir Hamzah, itself a rendition of an eleventh-century text in Persian. The protagonist Hamza was an uncle of the Prophet Muhammad. His epic story used to be told across Islamic Asia in a range of literary and performance genres. The text is Javanized not only in its language but also its poetics and (selectively) its natural and cultural settings. Among other things, Caritanira Amir helps to clarify the relationship between Middle and Modern Javanese, and it problematizes social, political, and religious issues that were evidently of concern in the early modern Java Sea world. Several appear in the excerpt presented here.